Effects of biological agents on rhizosphere microecological environment and nutrient availability for rice - Hang Zhou; Hang Zhou; Hang Zhou; Kaibo Yu; Lingli Nie; Lingli Nie; Lang Liu; Jianqun Zhou; Kunlun Wu; Kunlun Wu; Kunlun Wu; Honghong Ye; et al. (Frontiers in Microbiology)
As the world’s population grows, pursuing sustainable agricultural production techniques to increase crop yields is critical to ensuring global food security. The development and application of biological agents is of great significance in promoting the sustainable development of agriculture. This study aimed to investigate the role of JZ (compound microbial agent) and MZ (biological agent made from plant materials) in improving the rhizosphere microecological environment and nutrient availability for rice. This study found that JZ enriched Cyanobacteria with biological nitrogen fixation functions; spraying MZ can enrich some beneficial microbiota, such as Bradyrhizobium, playing a role in symbiotic nitrogen fixation. Meanwhile, JZ and MZ were found to affect rhizosphere soil metabolism and improve potassium and nitrogen availability. JZ may promote the degradation of fungicides in the rhizosphere soil environment. Overall, applying biological agents through optimizing rice growing environment to improve yield showed great potential.